Landscape analysis and land use evolution in the hydrographic basin of Barra Seca river, ES - Guarnier, Letícia; Oliveira, Fabricia Benda de; Fonseca, Vicente Sombra da; Oliveira, Carlos Henrique Rodrigues de (Ciência e Natura, 2018)
Multitemporal analysis for monitoring land cover and use is an important tool for understanding the evolutionary dynamics of a region, assisting the knowledge on the environmental reality. This study aimed at mapping the land cover classes of the Barra Seca River basin, in northern Espírito Santo, obtained using the Bhattacharya algorithm supervised classification in 1985, 1996, 2006 and 2016. The land use and occupation map allowed characterizing quantitatively the areas identified in the basin map in 10 classes as follows water bodies, agriculture and grasses, dense tree cover, sparse tree cover, exposed soil, wetlands, urban areas, rocky outcrops, shade, and clouds. The landscape maps were obtained using the Patch Analyst extension. In the studied time interval, the land use and occupation in the basin changed little, with areas dominated mostly by agriculture and grasslands, followed by forests while the basin vegetation area also remained mostly unchanged. However, the quantitative analysis using landscape metrics indicates an increasing fragmentation and edge effect in the Barra Seca River basin.